2014
DOI: 10.1158/1078-0432.ccr-14-0742
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of Overall Survival in Advanced Lung Adenocarcinoma Patients with the XAGE1 (GAGED2a) Antibody

Abstract: Purpose: The cancer/testis antigen XAGE1 (GAGED2a) is expressed in approximately 40% of advanced lung adenocarcinomas. We investigated the clinical relevance of the XAGE1 (GAGED2a) immune responses in patients with advanced lung adenocarcinoma.Experimental Design: The XAGE1 (GAGED2a) antigen expression and EGFR mutation were determined with tumor tissues. The XAGE1 (GAGED2a) antibody and T-cell immune responses, as well as immune cell phenotypes, were analyzed with blood samples. Patients with EGFR wild-type (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 38 publications
4
26
2
Order By: Relevance
“…Tumor‐infiltrating plasma cells produced the various specific antibodies to cancer‐testis antigens, such as LAGE‐1, the MAGE family, and NY‐ESO‐1 in lung cancer . In advanced lung cancer, the presence of circulating XAGE‐1 antibody to its cancer‐testis antigen indicated favorable survival in association with activating the antigen‐specific T cells . Tumor‐infiltrating plasma cells may be, at least in part, involved in anti‐tumor effects through the production of tumor‐specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor‐infiltrating plasma cells produced the various specific antibodies to cancer‐testis antigens, such as LAGE‐1, the MAGE family, and NY‐ESO‐1 in lung cancer . In advanced lung cancer, the presence of circulating XAGE‐1 antibody to its cancer‐testis antigen indicated favorable survival in association with activating the antigen‐specific T cells . Tumor‐infiltrating plasma cells may be, at least in part, involved in anti‐tumor effects through the production of tumor‐specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Ohue et al 27 recently reported that the expression of XAGE-1 was associated with poor prognosis and that the presence of anti-XAGE-1 antibody was strongly associated with prolonged OS in patients with advanced lung adenocarcinoma. Ohue et al 27 recently reported that the expression of XAGE-1 was associated with poor prognosis and that the presence of anti-XAGE-1 antibody was strongly associated with prolonged OS in patients with advanced lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The NY-ESO-1 + group also tended to have poorer outcomes than the negative group, yet the difference was not significant. In addition to the suggestion that CTA may be ideal targets for tumor-specific immunotherapy because of their tumor-restricted expression patterns, 7 previous studies have also indicated that CTA expression is associated with poorer disease-free survival and/or OS in a variety of cancers, such as melanoma, 25 non-small cell lung cancer, [26][27][28] ovarian cancer, 29 breast cancer, 30 multiple myeloma, 31 colorectal cancer, 32 bladder cancer, 33 prostate carcinoma, 34 vulvar cancer, 35 gastrointestinal stromal tumors, 36 squamous cell carcinoma 37 and stomach cancer. 38 Expression of NY-ESO-1 is reportedly associated with disease progression and poor prognosis in various cancers, including melanoma.…”
Section: (B)mentioning
confidence: 99%
“…Expression of CCR4, NY-ESO-1, and XAGE1 (GAGED2a) was examined by IHC as described previously (11,(19)(20)(21)(22).…”
Section: Ihcmentioning
confidence: 99%
“…The data were analyzed using FlowJo software (version 7.6.5; Tree Star). A number of TNFa-staining cells stimulated with XAGE1 (GAGED2a) OLPs that was more than 2-fold the number of staining cells stimulated with HIV gag control peptides (a mixture of MGARASVLSGGELDR and ASVLSGGELDRWEKI) was defined as positive (22).…”
Section: Intracellular Cytokine Stainingmentioning
confidence: 99%